2021
DOI: 10.3390/healthcare9060684
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Nosocomial Outbreak of Pantoea agglomerans Related to Parenteral Nutrition Procedures

Abstract: Pantoea agglomerans is a Gram-negative bacterium that infrequently infects humans. Most reports involving it are about infections in soft tissues or bone/joint infections caused by contamination from soil or penetrating trauma by vegetation, such as thorns and splinters. More frequently, it is found as an opportunistic pathogen in immunocompromised patients. It is not rare to find reports of bacteremia and sepsis from contamination of intravenous fluid, parenteral nutrition, blood products and anesthetic agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 35 publications
3
9
0
Order By: Relevance
“…In contrast, none of the patients in our dialysis unit had a recent history of thorn injuries. In concordance with our study findings, published data 2,5 also suggest a high predisposition of this infection in immunocompromised patients as seen by this infectious outbreak, predominantly in our dialysis patients who were diabetics, on immunosuppressives and with prior kidney transplantation. Published data have also suggested that past antibiotic exposure 2,29,30 can increase the risk of this infection.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In contrast, none of the patients in our dialysis unit had a recent history of thorn injuries. In concordance with our study findings, published data 2,5 also suggest a high predisposition of this infection in immunocompromised patients as seen by this infectious outbreak, predominantly in our dialysis patients who were diabetics, on immunosuppressives and with prior kidney transplantation. Published data have also suggested that past antibiotic exposure 2,29,30 can increase the risk of this infection.…”
Section: Discussionsupporting
confidence: 93%
“…However, it has the potential to cause even life-threatening complications such as sepsis, abscess, 17 infective endocarditis, pneumonia, 18 urinary tract infection, 18 septic arthritis, 19 neutropenic fever, 20 endophthalmites, 21 osteomyelitis, 22 and periostitis. 5 In hemodialysis patients, one study reported infective endocarditis of the mitral valve as a predominant complication associated with this infection. 3 Currently, there are limited studies on the occurrence of P. agglomerans infections in the dialysis population, with most focusing on peritonitis in peritoneal dialysis patients.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations